CRABP proteins – relatives or homonyms? - E. M. Tchevkina; I. A. Favorskaya (Успехи молекулярной онкологии, 2015)
Retinoic acid being the most active metabolite of vitamin A (retinol) regulates the wide spectrum of physiological processes including embryonic development, development of immune response, hematopoiesis, glucose and lipids metabolism, etc. Retinoic acid participates in the regulation of such important aspects of life-sustaining activity as cell differentiation, proliferation and programmed cell death. This review is focused on comparison of two highly homological members of lipid-binding proteins family, CRABP1 and CRABP2. Although binding of retinoic acid is the only known function of these proteins the physiological meaning this interaction seems to be rather different. CRABBP2 binding of retinoic acid leads to the activation of RAR / RXR nuclear receptors, that act as transcription factors, and further stimulation of expression of numerous retinoic responsive genes. The meaning of CRABP1 binding of retinoic acid is less clear. Some data evidences for the similar action of CRABP1 and CRABP2 in regard to the potentiation of the retinoic acid effect, while the majority of data points on the opposite role of CRABP1, that is reduction of intracellular concentration of retinoic acid and / or decrease of retinoic acid bioavailability through the potentiation of its catabolism or sequestration in the cytosol. The most recent publications also suggest some additional functions of these proteins that could be independent of retinoic acid signalling. The data concerning the roles of these proteins in carcinogenesis and tumor progression are contradictive as well.This review covers the functions of retinoic acid as well as the molecular mechanisms mediating its activity including the different aspects of retinoic acid receptors activity. The review also comprises the comparative structural-functional analysis of CRABP proteins and probable mechanisms of their intracellular activity including those associated with retinoic acid signalling and retinoic acid-independent. A special attention is drawn to the analysis of the data on the involvement of CRABP proteins in the carcinogenesis and tumor progression. The data pointing on either oncogenic or tumor-suppressive functions are given for each protein.